The Subversive Role of Verbal Aggression in the Sarcastic Language of Njuz.net - Jovanka Kalaba ([sic])
In the last years, Serbia has witnessed coming into being of various media forms that all provide social, political and cultural criticism through acrid comedy, parody and satire. The paper centers on sarcasm as one of the key aggressive rhetorical devices used in the language of popular satirical portal Njuz.net, with an overview of the structural and functional characteristics of sarcasm in contemporary communication. The paper explores how language aggressiveness manages to create an affirmative context in which the domineering structures of the official discourse are undermined by marginalized alternative discourses, as well as how such content, disseminated mainly through social networks and blogs and charged with verbal aggression and intertextual allusiveness stemming from deeper political, historical and social issues, succeeds in providing a narrative of kinship among those who often see it as the last recourse to sanity.Keywords: sarcasm, violence, language, popular culture, Njuz.net